Receptor tyrosine kinase-like orphan receptor 1 inhibitor strictinin exhibits anti-cancer properties against highly aggressive androgen-independent prostate cancer - Vignesh Sivaganesh; Bela Peethambaran (Open Exploration Publishing Inc., 2023)
Aim: It is important to identify anti-cancer compounds that can inhibit specific molecular targets to eradicate androgen-receptor negative (ARneg), androgen-independent (AI) prostate cancer, which is an aggressive form of prostate cancer with limited treatment options. The goal of this study was to selectively target prostate cancer cells that have high levels of oncogenic protein Receptor tyrosine kinase-like orphan receptor 1 (ROR1) by using strictinin, a small molecule ROR1 inhibitor. Methods: The methods performed in this study include western blots, methyl thiazolyl tetrazolium (MTT) proliferation assays, phosphatidylserine apoptosis assays, apoptosis flow cytometry (Annexin V, caspase 3/7), migration scratch assays, Boyden chamber invasion assays, and cell cycle flow cytometry. Results: Strictinin was most lethal against PC3 [half-maximal drug inhibitory concentration (IC50) of 277.2 µmol/L], an ARneg-AI cell type that expresses the highest levels of ROR1. Strictinin inhibited ROR1 expression, downstream phosphatidylinositol 3-kinase (PI3K)-protein kinase B (AKT)-glycogen synthase kinase 3beta (GSK3β) pro-survival signaling, and epithelial-to-mesenchymal transition markers in PC3 cells. Additionally, strictinin decreased PC3 cell migration and invasion, while increasing S-phase cell cycle arrest. In ARneg-AI DU145 cells, strictinin inhibited ROR1 expression and modulated downstream AKT-GSK3β signaling. Furthermore, strictinin exhibited anti-migratory, anti-invasive, but minimal pro-apoptotic effects in DU145 cells likely due to DU145 having less ROR1 expression in comparison to PC3 cells. Throughout the study, strictinin minimally impacted the phenotype of normal prostatic epithelial cells RWPE-1 (IC50 of 658.5 µmol/L). Strictinin was further identified as synergistic with docetaxel [combination index (CI) = 0.311] and the combination therapy was found to reduce the IC50 of strictinin to 38.71 µmol/L in PC3 cells. Conclusions: ROR1 is an emerging molecular target that can be utilized for treating prostate cancer. The data from this study establishes strictinin as a potential therapeutic agent that targets ARneg-AI prostate cancer with elevated ROR1 expression to reduce the migration, invasion, cell cycle progression, and survival of prostate cancer.